The influence of situational constraints on the perceived value of consulting services - Plenge, Nicole E.; Adair Erickson, Robin; Roloff, Michael E. (International journal of organizational analysis (2005), 2008)
Purpose - This article aims to examine how situational constraints impact clients' valuations of the task and socio-emotional resources exchanged when interacting with consultants. In consultant-client relationships, the emphasis on economic resources has commodified these interactions into explicit exchanges of time, money, and deliverables.Design methodology approach - A total of five hypotheses were tested using a within-subjects experimental design. Subjects consisted of 110 adult professionals who were presented with five different scenarios in a random sequence and asked to rank order and evaluate a list of professional-service resources.Findings - The valuation of resources was found to change when situational constraints were present. Regardless of the context, task resources were generally valued more than socio-emotional resources. When relational constraints were salient, socio-emotional resources were valued more in long-term than short-term relationships. When faced with time pressure or budgetary constraints, task needs were valued more than socio-emotional needs.Research limitations implications - There is potential bias due to snowball sampling, and the hypothetical nature of the experimental scenarios limits the generalizability of this study.Practical implications - For clients, this research indicates that the context surrounding consultant-client interactions plays an important role in shaping clients' valuation of resources, both individually and collectively. For consultants, these findings suggest that a "one-size-fits-all" strategy is not the most effective way to approach consultant-client interactions.Originality value - This study contributes to our knowledge about how situational constraints impact clients' valuation of the task and socio-emotional resources offered by consultants.